Role of Global Supply Chain Strategy in Control of Transfer Pricing in the EAEU Countries - Zauresh Zaurbekova (International Journal of Supply Chain Management, 2020)
Abstract— The article discusses features and problems of supply chain strategy in control of transfer pricing in member states of the Eurasian economic Union (EAEU). A comparative legal analysis of national legislation in the field of transfer pricing in the EAEU countries, in particular Armenia, Belarus, Kazakhstan, Kyrgyzstan and Russia, was carried out. The EAEU countries’ effectiveness in implementing international norms and standards in the studied area is evaluated. Special attention is paid to the implementation of the Base erosion and profit shifting (BEPS) Action Plan. The study defines the role of the Organization for Economic Cooperation and Development and the Eurasian Economic Commission in regulating transfer pricing in the EAEU. The study also considers issues of assigning transactions to the category of controlled transactions, determining market prices, and information exchange between regulatory authorities. d. The authors conclude with some observations about the nature of global supply chains, the value of international trade statistics and a hidden advantage of an integrated firm operating on a global scale the ability to somewhat arbitrarily select the activities to which profits should be allocated. For nation states, as supply chains become more international and complex, critical measures, such as gross domestic product, worker productivity, etc., are becoming ever more imprecise. The economic geography of cost of inputs and profits continue to separate as multinational enterprises drive the disaggregation of value creation and value capture. Based on the results of the analysis, recommendations were made regarding the coordination of EAEU countries’ efforts in the sphere of transfer pricing supply chain strategy.